A randomized controlled trial of the laryngeal mask airway for surfactant administration in neonates, - Rosilu F. Barbosa; Ana C. Simões e Silva; Yerkes P. Silva
Abstract Objective: To compare the short-term efficacy of surfactant administration by laryngeal mask airway versus endotracheal tube. Methods: Preterm infants (28-35 weeks of gestational age), weighing 1 kg or more, with respiratory distress syndrome, requiring nasal continuous positive airway pressure, with increased respiratory effort and/or fraction of inspired oxygen (FiO2) ≥ 0.40 to maintain oxygen saturation 91-95%, were randomized to receive surfactant by LMA following nCPAP or by ETT following mechanical ventilation (MV). The primary outcome was a clinical response defined as FiO2 ≤ 0.30 three hours after surfactant. Secondary outcomes for LMA group were: need of surfactant retreatment during the first 24 h, MV requirement, and presence of surfactant in gastric content. Results: Forty-eight patients were randomized; 26 in the LMA group and 22 in the ETT group. Six of 26 patients (23%) in the LMA group and five of 22 patients (22.7%) in the ETT group did not meet the primary outcome (p = 0.977). Fourteen (53.8%) of the LMA patients were not intubated nor ventilated; 12 (46.1%) were ventilated: for surfactant failure (23%), for nCPAP failure (11.5%), and for late complications (11.5%). Groups were similar regarding prenatal status, birth conditions, and adverse events. No significant gastric content was found in 61.5% of the LMA patients. Oxygen and second dose surfactant requirements, arterial/alveolar ratio, and morbidities were similar among groups. Conclusions: Surfactant administration by LMA showed short-term efficacy, with similar supplementary oxygen need compared to surfactant by ETT, and lower MV requirement. Further studies with larger sample size are necessary to confirm these results.